Vibration analysis of a single-walled carbon nanotube under action of a moving harmonic load based on nonlocal elasticity theory - Simsek, Mesut (ELSEVIER, 2010)
In the present study, forced vibration of a simply supported single-walled carbon nanotube (SWCNT) subjected to a moving harmonic load is investigated by using nonlocal Euler-Bernoulli beam theory. The time-domain responses are obtained by using both the modal analysis method and the direct integration method. The effects of nonlocal parameter, aspect ratio, velocity and the excitation frequency of the moving load on the dynamic responses of SWCNT is discussed. For comparison purposes, free vibration frequencies and static deflections of the SWCNT subjected to a point load at the midpoint are obtained and compared with previously published studies. Good agreement is observed. The results show that dynamic deflections of the SWCNT increase with increase in the nonlocal parameter, which means that dynamic deflections based on the local beam theory are underestimated, and the effect of nonlocal parameter is dependent on the aspect ratio. Furthermore, load velocity and the excitation frequency play an important role on the dynamic behavior of the SWCNT. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Vibration; Nonlocal elasticity theory; Carbon nanotubes; Moving loads; FUNCTIONALLY GRADED BEAM; PRESTRESSED DAMPED BEAM; TIMOSHENKO-BEAM; DYNAMIC-ANALYSIS; MODELS; FORCE; Science & Technology - Other Topics; Physics